The Politics of Uncertainty Challenges of Transformation - Scoones, Ian; Stirling, Andy (Taylor & Francis, 2020)
"Why is uncertainty so important to politics today? To explore the underlying reasons, issues and challenges, this book's chapters address finance and banking, insurance, technology regulation and critical infrastructures, as well as climate change, infectious disease responses, natural disasters, migration, crime and security and spirituality and religion. The book argues that uncertainties must be understood as complex constructions of knowledge, materiality, experience, embodiment and practice. Examining in particular how uncertainties are experienced in contexts of marginalisation and precarity, this book shows how sustainability and development are not just technical issues, but depend on deeply political values and choices. What burgeoning uncertainties require lies less in escalating efforts at control, but more in a new - more collective, mutualistic and convivial - politics of responsibility and care. If hopes of much-needed progressive transformation are to be realised, then currently-blinkered understandings of uncertainty need to be met with renewed democratic struggle. Written in an accessible style and illustrated by multiple case studies from across the world, this book will appeal to a wide cross-disciplinary audience in fields ranging from economics to law to science studies to sociology to anthropology and geography, as well as professionals working in risk management, disaster risk reduction, emergencies and wider public policy fields."